2022
DOI: 10.1093/oncolo/oyac138
|View full text |Cite
|
Sign up to set email alerts
|

Targeting CDK4 and 6 in Cancer Therapy: Emerging Preclinical Insights Related to Abemaciclib

Abstract: Pharmacologic inhibitors of cyclin-dependent kinases 4 and 6 (CDK4 and 6) are approved for the treatment of subsets of patients with hormone receptor positive (HR+) breast cancer (BC). In metastatic disease, strategies involving endocrine therapy combined with CDK4 and 6 inhibitors (CDK4 and 6i) improve clinical outcomes in HR+ BCs. CDK4 and 6i prevent retinoblastoma tumor suppressor protein phosphorylation, thereby blocking the transcription of E2F target genes, which in turn inhibits both mitogen and estroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 112 publications
0
11
0
Order By: Relevance
“…N-{5-[(4-ethylpiperazin-1-yl) methyl] pyridin-2-yl}-5-fluoro-4-[4-fluoro-1-isopropyl-2-methyl-1H-benzo (d) imidazol-6-yl] pyrimidin-2-amine (abemaciclib; LY2835219; Verzenio; Figure 1 ) is a selective, administered, ATP-competitive, and reversible kinase inhibitor of CDK4/6 ( Gelbert et al, 2014 ). Abemaciclib has several distinct chemical [2-anilino-2, 4-pyrimidine-(5-benzimidazole) scaffold], pharmacological (continuous dosing schedule), and clinical properties (single agent therapy) compared to palbociclib and ribociclib ( Yuan et al, 2021 ; Wander et al, 2022 ). Abemaciclib inhibits Rb phosphorylation and induces G1 cell cycle arrest, resulting in antitumor activity ( Gelbert et al, 2014 ; Wright and Md, 2021 ; Nardone et al, 2022 ; Nawa et al, 2022 ; Sun et al, 2022 ; Wander et al, 2022 ; Wang and Bao, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…N-{5-[(4-ethylpiperazin-1-yl) methyl] pyridin-2-yl}-5-fluoro-4-[4-fluoro-1-isopropyl-2-methyl-1H-benzo (d) imidazol-6-yl] pyrimidin-2-amine (abemaciclib; LY2835219; Verzenio; Figure 1 ) is a selective, administered, ATP-competitive, and reversible kinase inhibitor of CDK4/6 ( Gelbert et al, 2014 ). Abemaciclib has several distinct chemical [2-anilino-2, 4-pyrimidine-(5-benzimidazole) scaffold], pharmacological (continuous dosing schedule), and clinical properties (single agent therapy) compared to palbociclib and ribociclib ( Yuan et al, 2021 ; Wander et al, 2022 ). Abemaciclib inhibits Rb phosphorylation and induces G1 cell cycle arrest, resulting in antitumor activity ( Gelbert et al, 2014 ; Wright and Md, 2021 ; Nardone et al, 2022 ; Nawa et al, 2022 ; Sun et al, 2022 ; Wander et al, 2022 ; Wang and Bao, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Abemaciclib has several distinct chemical [2-anilino-2, 4-pyrimidine-(5-benzimidazole) scaffold], pharmacological (continuous dosing schedule), and clinical properties (single agent therapy) compared to palbociclib and ribociclib ( Yuan et al, 2021 ; Wander et al, 2022 ). Abemaciclib inhibits Rb phosphorylation and induces G1 cell cycle arrest, resulting in antitumor activity ( Gelbert et al, 2014 ; Wright and Md, 2021 ; Nardone et al, 2022 ; Nawa et al, 2022 ; Sun et al, 2022 ; Wander et al, 2022 ; Wang and Bao, 2022 ). Abemaciclib is a mainstay of HR + breast cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulation of CDK activity is frequently observed in cancer cells and plays critical roles in the development and progression of cancer and neurodegenerative disorders. (Lukasik et al 2021;Malhotra et al 2021;Malumbres and Barbacid 2009;Matthews et al 2022;Otto and Sicinski 2017;Wander et al 2022) CDK2 and CDK4 are frequently upregulated, excessively active and overexpressed in cancer cells including breast, lung, and prostate cancers, and adrenocortical carcinomas (Baker et al 2022;Lapenna and Giordano 2009;Liang et al 2020;Malumbres and Barbacid 2009;Wu et al 2011;Zhang et al 2021a), making them promising drug discovery targets. (Baker et al 2022;Lapenna and Giordano 2009;Liang et al 2020;Wu et al 2011;Zhang et al 2021a) Inhibiting them can impede cell cycle progression, curtailing cell division and proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…(Fassl et al 2022) The activity of CDK4 is often increased in cancer cells due to genetic mutations, amplifications, and overexpression of upstream nodes in the signaling pathways and in its regulatory cyclin-D. CDK4 plays a crucial role in the G1 phase-the longest phase of the cell cycle-making it an important target for cancer therapy. (Adon et al 2021;DeMichele et al 2015;Lim et al 2016;Vijayaraghavan et al 2018;Wander et al 2022) CDK2, activated by cyclin-E binding in the G1/S transition also acts in DNA damage repair. (Tadesse et al 2019) Significantly, although mutations in CDK2 and CDK4 genes have been identified in some cancer cells, different than other kinases such as PI3K (Galdadas et al 2020), their frequency is low, especially in the catalytic domain, as shown in The Cancer Genome Atlas (TCGA) and Genomics Evidence Neoplasia Information Exchange (GENIE) databases, (Otto and Sicinski 2017) emphasizing the severe outcome of their mutations.…”
Section: Introductionmentioning
confidence: 99%